Physical and Chemical Characteristics of Modified Sweet Potato Flour (Ipomoea batatas (L.) Lam) Based on Fermentation Duration and Yeast Concentration - Lisna Widyatikta, Athifa; Eris, Fitria Riany; Yoesepa Pamela, Vega; Ahmad Riyanto, Rifqi (Department of Technology of Agricultural product (THP) Jambi University, 2025)
The high consumption of wheat-based products in Indonesia has encouraged the development of local flour alternatives. This study aimed to modify honey sweet potato flour through fermentation using tapai yeast and to evaluate how fermentation duration and yeast concentration affect its physicochemical and functional characteristics. This study employed a Split-Plot Design with a Factorial Randomized Block Design as the control design. It consisted of two factors and two repetitions. The results showed that the modification significantly improved the quality of the flour: the whiteness degree increased from 73.80 to 83.72. At the same time, the moisture content decreased from 11.49% to 7.60%, aligning with the Indonesian National Standard (SNI 7622:2011). The fermentation also reduced ash content (from 2.10% to 0.58%) and pH (from 5.55 to 3.97) while enhancing amylose levels (up to 29.88%), indicating starch restructuring and improved flour purity. Morphological analysis revealed that starch granules changed from smooth and compact to porous and irregular, enhancing the water-holding capacity (276.83%) and reducing viscosity (135.00 cP). The best treatment, 36-hour fermentation with 5% tapai yeast, produced stable flour with desirable swelling power and functional properties, suggesting potential for bakery and noodle applications.